Web Information Retrieval System for Technological Forecasting - Montiel, Raúl (2017)
Technological Forecasting and Competitive Intelligence are two different disciplines that, used together, provide the organizations with an invaluable analytic tool for the environment and the competing companies’ behavior. This kind of technology can be used for extracting useful information to make strategic decisions. This paper describes a Web mining system which gathers the users’ information requirements through a series of guided questions, constructs various search keys with the answers and uses them to perform a continuous search and analysis process by means of several web search engines and different information retrieval algorithms to score the relevance of the documents obtained. These documents are later presented to the user as an aid in the decision making process. After the description, the system was tested in several scenarios and the obtained results are shown and discussed.